Pengaruh Model Eliciting Activities Terhadap Kemampuan Penalaran Matematis Siswa pada Materi Persamaan Linear Satu Variabel - Norma Sukma Amelia (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to examine the effect of the Model Eliciting Activities (MEAs) model on students’ mathematical reasoning abilities. It also sought to determine differences in reasoning performance between students taught using MEAs and those receiving conventional instruction on One Variable Linear Equations (PLSV). The study employed a Quasi-experimental approach using a Nonequivalent Control Group Design at MTsN 5 Jember. The research population consisted of all eighth-grade students. Class VIII A served as the experimental group and class VIII C as the control group. Both groups were selected through cluster random sampling, with 21 students in each group. Data were collected through a validated mathematical reasoning test. Data analysis was conducted using the Paired Sample T-test and the Independent Sample T-test. The findings revealed two main results. First, the MEAs model had a significant effect on students’ mathematical reasoning abilities. The experimental group’s mean score increased from 52.24 (Standard Deviation = 11.23) in the pretest to 81.26 (Standard Deviation = 8.39) in the posttest, with a significance value of 0.000 (p < 0.05). Second, there was a statistically significant difference between the two groups. The experimental group’s posttest mean score was 81.26 (Standard Deviation = 8.39), which was higher than the control group’s mean score of 63.69 (Standard Deviation = 14.57). The study concludes that the MEAs model is more effective than conventional learning methods in improving students’ mathematical reasoning abilities. This effectiveness is supported by the systematic and contextual modeling processes within the MEAs framework. These processes encouraged students to construct mathematical models independently through real world problem-solving activities.
Approved by Teddy
Keywords: Aljabar; Kemampuan Penalaran Matematis; Model Eliciting Activities Activities